HIV/AIDS epidemic in Malaysia : vulnerability and risk of women - Mondal, Md. Nazrul Islam; Shitan, Mahendran (Asian Online Journals, 2013)
Malaysia is no exception to the growing trend and severity in Human immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) cases where women are more vulnerable than men. Consequently, the incidence of HIV infections in females is steadily increasing. This study aimed to explore the HIV vulnerability of women and the inequity of HIV infections between males and females in Malaysia over time. Data and necessary information were obtained from the Ministry of Health, Malaysia. The analyses were done by polynomial curve fitting and discriminant function analysis. The fifth degree polynomials were found as useful fitting models for all the cases and almost all the curves explained more than 95% of the variation. The discriminant function analysis identified the discrimination among males and females HIV/AIDS prevalence and AIDS deaths. The current study identified the discrimination between males and females HIV and AIDS prevalence, and AIDS deaths over time and HIV infections among women are gradually rising. The findings suggested that the policies should be aimed at to reduce the major risk factors of HIV transmission, including injecting drug use, needle sharing, and unprotected sex.